FARINHA DO MESOCARPO DE BABAÇU EM DIETAS PARA OVINOS CONFINADOS - SANTOS, Paull Andrews Carvalho dos (2015)
The aim of this experiment was to evaluate the performance and the breeding soundness profile of feedlot lambs, which were fed with increasing levels of babassu mesocarp flour (0, 10, 20 and 30%). Were used 20 male sheep, not castrated without defined breed, with an average age of 150 days and average body weight of 21.57±3.53 kg. The animals were distributed in randomized block design with 4 treatments and 5 replications. The experimental period was 59 days of confinement (9 days for adaptation and 50 days for data collection). Were determined the intakes and digestibility of dry matter and nutrients and water intake. The body performance was evaluated by values of weight gain, body condition score, ribs eye area and subcutaneous fat thickness. To evaluate the breeding soundness profile were carried out examinations of testis size and sperm. The estimate of the economic viability was based on the gross profit margin calculation. It was found that the inclusion of babassu mesocarp flour up to 20% of dry matter in the diet of feedlot lambs does not influence the intake of dry matter, organic matter, crude protein, total carbohydrates and non-fibrous, as well as the daily average and total weight gain, feed conversion, water intake, testis size and semen quality. The digestibility of dry matter, organic matter, crude protein and neutral detergent fiber decreases from the inclusion of 20% of babassu mesocarp flour in animal diets. The inclusion of 20% of babassu mesocarp flour in the diet of animals provided positive gross profit margin.